DT389-YP7, a Recombinant Immunotoxin against Glypican-3 That Inhibits Hepatocellular Cancer Cells: An In Vitro Study - Hamid Hashemi Yeganeh (MDPI AG, 2021)
Hepatocellular carcinoma (HCC) is one of the high-metastatic types of cancer, and metastasis occurs in one-third of patients with HCC. To maintain the effectiveness of drug compounds on cancer cells and minimize their side effects on normal cells, it is important to use new approaches for overcoming malignancies. Immunotoxins (ITs), an example of such a new approach, are protein-structured compounds consisting of toxic and binding moieties which can specifically bind to cancer cells and efficiently induce cell death. Here, we design and scrutinize a novel immunotoxin against an oncofetal marker on HCC cells. We applied a truncated diphtheria toxin (DT389) without binding domain as a toxin moiety to be fused with a humanized YP7 scFv against a high-expressed Glypican-3 (GPC3) antigen on the surface of HCC cells. Cytotoxic effects of this IT were investigated on HepG2 (GPC3+) and SkBr3 (GPC3−) cell lines as positive- and negative-expressed GPC3 antigens. The dissociation constant (Kd) was calculated 11.39 nM and 18.02 nM for IT and YP7 scfv, respectively, whereas only IT showed toxic effects on the HepG2 cell line, and decreased cell viability (IC50 = 848.2 ng/mL). Changing morphology (up to 85%), cell cycle arrest at G2 phase (up to 13%), increasing intracellular reactive oxygen species (ROSs) (up to 50%), inducing apoptosis (up to 38% for apoptosis and 23% for necrosis), and an almost complete inhibition of cell movement were other effects of immunotoxin treatment on HepG2 cells, not on SkBr3 cell line. These promising results reveal that this new recombinant immunotoxin can be considered as an option as an HCC inhibitor. However, more extensive studies are needed to accomplish this concept.